An Impact of Prolonged Electrolysis on the Electrochemical Performance and Surface Characteristics of NiFe-Modified Graphite Electrodes for Alkaline Water Electrolysis - Mateusz Kuczyński; Tomasz Mikołajczyk; Bogusław Pierożyński; Mirosław Bramowicz; Sławomir Kulesza (Molecules)
This study investigates the influence of prolonged electrolysis on the electrochemical performance and surface characteristics of NiFe-modified compressed graphite electrodes used in alkaline water electrolysis. The electrochemical experiment was conducted over a two-week period at a constant temperature of 60 °C. The electrodes were evaluated for changes in surface morphology and composition using scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDS), and X-ray diffraction (XRD). The results demonstrated stable electrochemical performance with minimal current variation. However, significant structural changes occurred, including the formation of new microstructures on the cathode and the emergence of KHCO3 (potassium bicarbonate) compound on both electrodes. Crystallographic analysis revealed an increase in crystallite size and tensile lattice strain on the cathode, while the anode exhibited compressive lattice strains and a reduction in crystallite size. These findings suggest that the observed changes were driven by electrochemical annealing processes, contributing to material redistribution and surface modifications during prolonged electrolysis. This study provides insight into optimizing NiFe-based catalysts for enhanced durability and efficiency in water splitting technologies.